Synthesis, self-association and chiroselectivity of isotopically labeled trianglamine macrocycles in the ion trap mass spectrometer - Kuhnert, Nikolai; Le-Gresley, Adam; Nicolau, Daniel C.; Lopez-Periago, Ana (Journal of labelled compounds & radiopharmaceuticals, 2007)
The synthesis and self‐association of chiral isotopically labeled trianglamine macrocycles under electrospray mass spectrometer conditions in an ion trap are described. A moderate diastereoselectivity in the self‐association process was observed providing a synthetic model system for the investigation of chiral self‐association in the gas phase. The first non‐covalently bound dimer exclusively bonded through aromatic–aromatic interactions was observed in the gas phase. Evidence for self‐association in solution was observed by diffusion nuclear magnetic resonance spectroscopy. Copyright © 2007 John Wiley & Sons, Ltd. The synthesis and self‐association of chiral isotopically labeled trianglamine macrocycles under electrospray mass spectrometer conditions in an ion trap are described. Copyright © 2007 John Wiley & Sons, Ltd.